Asuhan Keperawatan Pada An. N Dengan Gangguan Kardiovaskuler : Penyakit Jantung Bawaan Di Ruang Cempaka III RSUD Pandan Arang Boyolali - Kurniawan, Risky Rahmat, Agus Sudaryanto, S.Kep., Ns., M.Kes (2015)
Background : Infant and child mortality rate caused by Congenital Heart Disease quite high in both developed countries and developing countries (including Indonesia). With a population of 235 million in Indonesia, it was estimated that 50,000 babies would born with congenital heart disease so that the number of prevalence was quite high. Lack of parents'knowledge and attention towards congenital heart disease one of the problems in handling children with congenital heart disease. It was required a sophisticated medical treatment so that children are able to survive soon after their birth. Objective : To implement nursing care in patients with congenital heart disease include assessment, intervention, implementation and evaluation of nursing care. Methods : The method used was case study approach that was defined as a scientific menthod to collect data, analyze the data method was to collect data, analyze the data and draw conclusions. Results :The emerging diagnosis on the case were of decreased cardiac output related to malformations ofthe heart, ineffective breathing pattern related to pulmonal congestion and intolerance activity were related to the imbalance of oxygen consumption by body and supply of oxygen to the cells. After 3x24 hours nursing care,it was obtained that intolerance activity was resolved, decreased heart output did not occur and breathing pattern effective. Conclusion : The written was doing nursing care, intolerance activity was resolved, ineffective breathing pattern were partially resolved and decreased heart output was not resolved so thus required further treatment and cooperation with other medical team. Keywords: Congenital Heart Disease (CHD), shortness of breath, weakness, cardiac abnormality, decreased cardiac output.